The Influence of Leadership and Organizational Culture on Employee Performance at the Ground Transportation Management Office in Region XIII of East Nusa Tenggara Province, Mediated by Work Motivation and Work Discipline - Jermias Meda; Simon Sia Niha; Anggraeny Paridy; Henny Angri Manafe (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
This study aims to examine the impact of leadership, organizational culture, work motivation, and work discipline on employee performance at the Ground Transportation Management Office in Region XIII of East Nusa Tenggara Province. The sampling technique employed is saturated or census sampling. The research utilizes a statistical testing tool known as Partial Least Square (PLS) based on variance structural equation modeling, implemented through the SmartPLS software. The findings indicate that leadership significantly and positively influences employee performance, whereas organizational culture lacks a significant impact. Both leadership and organizational culture affect work motivation, which, in turn, has a positive correlation with employee performance. Additionally, work motivation serves as a mediator between leadership and employee performance. However, work discipline does not significantly mediate the relationship between leadership and employee performance, nor does it mediate the connection between organizational culture and employee performance.